Molecular identification of Pichia guillermondii isolated from mine water acidic of Peru and its resistance to heavy metals - Orbegozo, Jeanette (2008)
Microbe eukaryotes like fungi and protista are common in the drainage of mines. Few information is known on microbial diversity of acid drainages of Peruvian mines. In this work we isolated and characterized the 1M9 yeast. We utilized LSU D1/D2 of the 26S rRNA gene sequence phylogenetic analyses to characterize the diversity the yeast 1MA9 isolated. The strain 1MA9 was closely related to the Pichia guilliermondii. The yeast showed high resistance to Mn2+ (>400 mM), intermediate to ions Zn2+ and Co2+ (400—600 mM), but sensible to ions Cu2+. This work provides the first data on yeasts from an aquatic acid environment of Peruvian mines.